2015
DOI: 10.1037/a0036526
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ethnic group variation on victimization and help seeking among Latino women.

Abstract: Interpersonal violence research on Latinos has largely ignored the ethnic group variations that are included under the pan-ethnic term Latino. The current study adds to the literature by utilizing a national sample of Latino women to examine the interpersonal victimization experiences and help-seeking responses to victimization by ethnic group. The sample was drawn from the Sexual Assault Among Latinas Study (SALAS; Cuevas & Sabina, 2010) that surveyed 2,000 self-identified adult Latino women. For the purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
2
35
0
1
Order By: Relevance
“…Similar results were found by French, Kim, and Pillado (2006). Other research suggests, however, that ethnic identity does protect against the negative effects of victimization for Latinas (Sabina, Cuevas, & Schally, 2015) but not self-harm (Chesin & Jeglic, 2012). It is vital to empirically unpack the complex relationship between ethnic identity and criminogenic outcomes to gain insight into within-group differences (Delgado & Stefancic, 2012; Solorzano & Delgado Bernal, 2001) as well as to develop culturally specific programs that promote well-being (e.g., Wright & Zimmerman, 2006).…”
Section: Ethnic Identitysupporting
confidence: 74%
“…Similar results were found by French, Kim, and Pillado (2006). Other research suggests, however, that ethnic identity does protect against the negative effects of victimization for Latinas (Sabina, Cuevas, & Schally, 2015) but not self-harm (Chesin & Jeglic, 2012). It is vital to empirically unpack the complex relationship between ethnic identity and criminogenic outcomes to gain insight into within-group differences (Delgado & Stefancic, 2012; Solorzano & Delgado Bernal, 2001) as well as to develop culturally specific programs that promote well-being (e.g., Wright & Zimmerman, 2006).…”
Section: Ethnic Identitysupporting
confidence: 74%
“…Intimate partner abuse exists in an ethnocultural context that shapes women's perceptions, influencing the labels attached to such experiences, levels of psychological distress, as well as disclosure and help-seeking behaviors (Mechanic & Pole, 2013;Sabina, Cuevas, & Schally, 2015). Whether or not acts of partner abuse are conceptualized as "sexual assault" and/or disclosed to others is shaped by the cultural context of women's lives, making these decisions strongly culture bound (Kasturirangan & Williams, 2003;Sabina et al, 2015).…”
mentioning
confidence: 97%
“…Whether or not acts of partner abuse are conceptualized as "sexual assault" and/or disclosed to others is shaped by the cultural context of women's lives, making these decisions strongly culture bound (Kasturirangan & Williams, 2003;Sabina et al, 2015). When cultural values emphasize collective over individual well-being, values stemming from familismo, such as the importance of family preservation over individual needs, may override personal safety considerations, thereby influencing whether, how, and to whom such acts are disclosed, as well as the nature and extent of help-seeking efforts (Fuchsel, 2013;Fuchsel, Murphy, & Dufresne, 2012;Galanti, 2003).…”
mentioning
confidence: 99%
“…In a study of interpersonal victimization patterns among Latinas, researchers found that 63% of Latinas who reported being victimized had experienced more than 1 victimization incident in their lifetime with women reporting from 1 to 10 total victimizations and an average of 2.56 victimizations (Cuevas et al 2012b). Another study using the same data set found that Latinas experienced multiple configurations of IPV victimization including physical, sexual, stalking, and threats (Sabina et al 2015a).…”
Section: Prevalence Of Ipv Among Latinasmentioning
confidence: 99%